"Your Health Essential for Your Hajj": Muslim pilgrims' knowledge, attitudes and practices regarding Middle East respiratory syndrome coronavirus (MERS-CoV) during Hajj season. Issue 5 (May 2017) - Alhomoud, Faten; Alhomoud, Farah
Abstract: Background: Up to date, there have been no studies to evaluate pilgrims' knowledge, attitude and practices regarding MERS-CoV during the annual Hajj pilgrimage in order to see whether there is a need for these aspects to be improved. Methods: A cross-sectional survey study was conducted with a convenience sampling. Participants were pilgrims, aged over 18, and able to speak Arabic or English. A self-administered structured questionnaire was distributed during Hajj season in Mecca. Descriptive and multiple linear regression analysis were used in data analysis. Results: Two hundred and fifty-seven participants completed the study, 80% of whom were female, and the median (IQR) age was 35 (24.5–43.5) years. Pilgrims had moderately correct knowledge and accurate attitudes about MERS-CoV with median scores of 5 (IQR 4–7) and 6 (IQR: 5–7) respectively. Educational level and employment status were significantly associated with knowledge whereas gender and age were significantly associated with attitude and practices respectively (P < 0.05). The correlation between knowledge, attitude and practices was significant (correlation coefficient: 0.207; P < 0.05). Better knowledge was found to be a predictor for positive practice. Conclusions: These findings will provide insight when designing future interventions to promote specific messages to enhance knowledge, change attitude and improve practice regarding MERS-CoV.